Potensi Konflik dalam Relasi Penjeratan Hutang di Masyarakat Nelayan: Studi Kasus Relasi Bakul dan Langgan di Desa Gebang Mekar Kabupaten Cirebon - Sulistyani, Wanodyo; Nulhaqim, Soni A. (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2016)
Debt bondage is a relation pattern between Bakul (the capital owner) and Langgan (fishers who are indebted to Bakul) in Gebang Mekar Village, Cirebon District. This debt bondage are imperishable because the lack of Langgan’s ability to pay their debt to Bakul; while Bakul as the capital owner has power to determine the price of fish and other fisheries products, where the fishers have obligation to sell their harvest to their Bakul. Yet, Bakul’s price is lower than the market price. As a result, to increase the fishers’ profit, they sold their harvest to other Bakul; this behavior is potentially raised a conflict between fishers and their Bakul also among Bakul. Study of Criminology explained the relation between the powerful and the powerless in making law in their favor. Unfair law has encouraged the powerless to breaking the law, and creating conflict. In this article, initially, the lack of fishers’ welfare related to the role of the state will be reviewed; next, the criminology theories which explain about violation and the causes of conflict will be outlined; furthermore, the relation between Bakul and Langgan in Gebang Mekar Village, Cirebon District will be described; lastly, potential conflict that arise because of Bakul and Langgan relation will be analyzed with criminology theories.Keywords: Conflict, social Relation, Fishery Community.